Pengembangan E-Modul Berbasis Inkuiri Terbimbing pada MateriKalor SMP Kelas VIII - Nidayati, Yura; Widayanti, Widayanti; Effendi, Effendi (Pendidikan Fisika Universitas Nurul Huda, 2025)
This research aims to: 1) develop a guided inquiry-based e-module on the subject of Natural Sciences (IPA) heat materials; 2) find out the students' responses after using guided inquiry-based e-modules on the heat material of junior high school grade VIII; and 3) to determine the feasibility of the E-Module based on guided inquiry. This research is a type of development research (Research and Development) with a 4D development model design which includes (define, Design, Develop, Disseminate). This research was carried out until the third stage, not until the fourth stage of dissemination but only to the development stage. Because this study looks at feasibility/validation, it does not reach the stage of widespread spread. The data collection instrument used in this study was in the form of validation sheets given to 6 validators, namely 3 media experts and 3 material experts. The type of data produced is quantitative data that is analyzed with the criteria guidelines of the assessment category to determine the quality of the product. The results of the analysis obtained in this study are based on the assessment: 1) media experts obtained an average of 0.87% including the Very Valid category. 2) material experts obtained an average of 0.88%. including the VeryValid category. 3) The feasibility of the product in the guided inquiry-based e-module with the percentage of field trials has met the average of 80% including the Very High category. The results show that the E-Module is worth using.